Student-teacher closeness and conflict in students with and without special educational needs - Sofia Freire; Pipa, J.; Aguiar, C.; Silva, F.; Moreira, S. (British Educational Research Journal, 2020)
Teachers play a key role in creating effective conditions for students to succeed in school. The quality of student-teacher relationships is consistently associated with social, emotional, behavioural, and academic adjustment and it is even more relevant for students with special educational needs (SEN), considering these students’ emotional, social, and learning vulnerabilities. This study aimed to examine the associations between students’ externalizing and internalizing behaviour, social skills, and academic performance, and teachers’ perceptions of conflict and closeness in their relationships with students with and without SEN. Data regarding 360 students of Year 3rd, Year 5th, and Year 7th grades (169 students with SEN) were collected. Teachers (n = 74) reported on student-teacher relationship and students’ social skills, behaviour problems, and academic performance. Special education teachers (n = 38) provided information regarding the diagnosis and profile of functioning of students with SEN. Results showed that teachers’ reports of students’ social skills and externalizing problems were the strongest predictors of closeness and conflict. Internalizing problems and SEN status also predicted decreased closeness, despite smaller effects. Taken together, findings support the importance of professional development opportunities focusing on facilitating teachers’ relationships with students with perceived challenging behaviour.